Implementation of ISO 6142- Gas Analysis - Preparation of Calibration Gas Mixtures - Gravimetric Method: Composition Determination and Uncertainty Estimation of Gas Reference Material - Muhammad Rizky Mulyana; Harry Budiman; Oman Zuas (Jurnal Penelitian Pendidikan IPA, 2020)
Reference material plays an important role in determining the validity of measurement results based on SNI ISO/IEC 17025: 2017. In order to obtain a valid and accurate composition, the standard procedure for making gas reference material has been regulated in ISO 6142. Thus, this article will discuss in detail about the determination of the reference material composition along with its uncertainty based on ISO 6142. Starting with the results of a precise weighing, the concentration of each component of the gas reference material is determined gravimetrically and verified by analytical methods, one of which is gas chromatography (GC). The concentration uncertainty of each component is a combination of the contribution from repeatability of the weighing results, the uncertainty of the composition of the gas raw material, the molecular mass of the gas component, and the total uncertainty of the reference material verification. It is hoped that the detailed discussion in this article can improve the competence of stakeholders in the field of gas measurement in determining the composition of gas reference material concentrations and estimating uncertainty.